Development of a Pd-Ag H2-selective membrane microchannel reactor for efficient solar hydrogen production with ammonia. (15th October 2022) - Xia, Qi; Lin, Liangrui; Lin, Zihan; Chen, Chen; Jin, Weiya; Liu, Qibin
Highlights: A Pd-Ag H2 -selective membrane microchannel reactor is developed. Not only the conversion but also the efficiency is improved by the reactor. The investigations of judging if mass and heat transfer limitations are presented. The maximum overall energy efficiency of 31.0% is obtained. Abstract: Ammonia is one of the most promising hydrogen carriers, which realizes storing and releasing hydrogen with ammonia synthesis and decomposition, respectively. Solar-driven ammonia decomposition is a carbon-free way to release hydrogen with solar energy. Recently, there have been lots of researches conducted to enhance the conversion of ammonia decomposition including improving noble-metal-based catalysts and developing membrane reactors. However, critical information regarding the reactor efficiency under solar radiation is hardly provided. Additionally, the heat and mass transfer process in the membrane reactor under the solar radiation need be further enhanced for an efficient thermochemical conversion. In this paper, a novel solar driven ammonia decomposition microchannel reactor integrating with palladium-argentum hydrogen-selective membrane is proposed. The reactor is not only with enhanced heat and mass transfer performance but also improved conversion by separating hydrogen simultaneously. A two-dimensional membrane microchannel reactor model has been developed to study the proposed reactor. The model has been validated by comparing the model-predicted results with the experimental data from references. Moreover, the effects of reactor inlet temperature, sweep gas flow rate, ammonia flow rate and retentate layer height on the reactor performance have been investigated parametrically. Learned from the results, the maximum conversion of 91% does not correspond to the maximum thermochemical conversion efficiency or overall energy efficiency, which are 23.1% and 30.7%, respectively. The maximum thermochemical conversion efficiency of 23.3% and overall energy efficiency of 31.0% have been obtained. The study provides valuable information regarding the thermochemical performance of the novel solar membrane microchannel reactor. Further, the meaningful investigations of judging if mass and heat transfer limitations occur are presented.